1114 Predicting lost productive time and medical cost due to poor psychosocial working conditions: a one-year prospective study. (24th April 2018) - Kawakami, N; Imamura, K; Baba, T; Asai, Y; Tsutsumi, A; Shimazu, A; Inoue, A; Hiro, H; Odagiri, Y; Yoshikawa, T; Yoshikawa, E
Abstract : Introduction: It is still not clear how much future excess cost for employers and the society are related to the poor psychosocial working conditions. Such prediction may be useful to prioritise interventions to improve psychosocial working conditions in the workplace. Methods: A baseline survey was conducted of Japanese monitors registered to an Internet survey company who were employed (in December 2015 or February 2016). Out of 5150 respondents, 3875 full-time employees were surveyed about one year later (in December 2016). The questionnaire asked respondents their psychosocial working conditions: job strain (the ratio of job demands to job control), interpersonal conflict, supervisor and coworker support, measured by the Brief Job Stress Questionnaire; and effort-reward imbalance, measured by a 10-item ERI questionnaire. The questionnaire also measured lost productive time that was converted into lost labour cost; and total medical expenditure in the past month assessed by TiC-P (Bouwmans, et al., 2013). Multiple linear regression analysis was conducted of the one-year increase in the total monthly cost at follow-up on the five psychosocial working conditions, adjusting for sex, age, occupation, and the cost at baseline. Result: A total of 2498 (64%) respondents completed the follow-up questionnaire; 43% were men; average age was 42 years old. Interpersonal conflict and ERI significantly and positively correlated with the increased total cost (p<0.001, 8, 278 JPY and 11, 047 JPY, respectively, for 1SD change); coworker support significantly and negatively correlated (p=0.001, –10, 583 JPY for 1SD change). These three factors significantly correlated with lost labour cost (p<0.001). ERI significantly and positively correlated with medical cost (p=0.030). Discussion: Poor psychosocial work conditions well predicted excess labour and medical cost at one-year follow-up. Improving interpersonal conflict, ERI, or coworker support by 1SD of the score would benefit for saving the total cost of 8000 to 11, 000 JPY per month.